2017
DOI: 10.1016/j.ajem.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of  upright patient positioning and intubation success rates At two academic EDs

Abstract: In our study emergency medicine residents had a high rate of success intubating in the upright position. While this does not demonstrate causation, it correlates with recent literature challenging the traditional supine approach to intubation and indicates that further investigation into optimal positioning during emergency department intubations is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 26 publications
5
53
0
1
Order By: Relevance
“…In a broad patient cohort undergoing general anesthesia in the operating room, elevating the head was associated with improved glottic view, reduced intubation difficulty, less need for ancillary maneuvers, and shorter intubation times compared with a supine body position or simple head extension . In an observational study of 231 ED intubations performed by residents, the ramped patient position was associated with improved first‐pass success compared to supine positioning . In a retrospective study of 528 emergent in‐hospital intubations, the ramped patient position, compared to supine, was associated with reduced odds of a composite of complications including difficult intubations, esophageal intubations, hypoxemia, or aspiration .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a broad patient cohort undergoing general anesthesia in the operating room, elevating the head was associated with improved glottic view, reduced intubation difficulty, less need for ancillary maneuvers, and shorter intubation times compared with a supine body position or simple head extension . In an observational study of 231 ED intubations performed by residents, the ramped patient position was associated with improved first‐pass success compared to supine positioning . In a retrospective study of 528 emergent in‐hospital intubations, the ramped patient position, compared to supine, was associated with reduced odds of a composite of complications including difficult intubations, esophageal intubations, hypoxemia, or aspiration .…”
Section: Discussionmentioning
confidence: 97%
“…17 In an observational study of 231 ED intubations performed by residents, the ramped patient position was associated with improved first-pass success compared to supine positioning. 18 In a retrospective study of 528 emergent in-hospital intubations, the ramped patient position, compared to supine, was associated with reduced odds of a composite of complications including difficult intubations, esophageal intubations, hypoxemia, or aspiration. 19 Results from randomized trials in both the ICU and the operating room have shown mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Although intubation is commonly undertaken in the supine position, recent published reports suggest that elevating the patient's head to a more upright position (20–45°) could improve preoxygenation, increase the probability of first‐pass success, and decrease intubation‐related adverse events (e.g., hypoxemia) …”
Section: Preparationmentioning
confidence: 99%
“…Furthermore, as adjunctive strategies such as ramp positioning (12)(13)(14) and apneic oxygenation (15,16) have become increasingly recognized as potentially beneficial, a continuous training curriculum provides opportunities for evaluating trainees' knowledge of these techniques and reinforcing their incorporation into airway management.…”
Section: Discussionmentioning
confidence: 99%